A quantitative and qualitative study on university students’ perceptions of soy-based food products and the aspects that influence these perceptions - Azhar, Sadaf (Kansas State University, 2024)
With the global population expected to surpass nine billion by 2025, there is an urgent need for sustainable plant-based protein alternatives. Soybeans, rich in essential amino acids, have emerged as a leading alternative protein source. This research investigates university students’ perceptions, knowledge, and consumption patterns of soy-based food products, leveraging both qualitative and quantitative research methods, and develops a scalable soy taco crumble for university dining services. The initial phase of the study employed a qualitative research design using focus group discussions to explore students’ perceptions of soy-based food products. Participants were recruited through a pre-survey and by posting flyers in the university dining centers and residence halls, resulting in two focus groups, each consisting of five and six participants. Discussions, guided by a structured questionnaire, were audio-recorded, transcribed, and analyzed using thematic analysis. Six main themes emerged: 1) awareness of soybeans and soy products was influenced by past experiences and exposure, either geographical or educational; 2) participants had limited knowledge about soy's nutritional value but recognized it as a protein source; 3) a preference for familiar foods was noted, but participants were receptive to innovative products; 4) a preference for new soy products in savory dishes were favored, culinary insights were shared; 5) concerns about soy-related stigma were highlighted; and 6) a preference for well-organized infographics was emphasized. These findings underscore the need for educational initiatives to raise awareness about soy's nutritional benefits and suggest that product development should balance familiarity and innovation to cater to diverse tastes. In the second phase, an online survey was conducted to quantitatively assess students’ attitude, social norms, and perceived behavioral control concerning the intention to consume soy-based food products, leveraging the Theory of Planned Behavior (TPB) as a framework. The survey targeted students' dining at the university’s dining centers, with seventy-six respondents completing the survey. The study created four infographics with different titles (meat-alternative protein, plant-based protein, soy-based protein, and soybean-based protein) to determine the effectiveness of infographics in influencing consumer consumption behavior. Results indicated that all infographics positively influenced students' intentions to consume soy-based foods. The "plant-based protein" infographic showed the highest reliability (α=0.808), followed by "soy-based protein" (α=0.736). Positive attitudes had a strong correlation with intention across all infographics, with coefficients ranging from 0.623 to 0.784 (p<0.001). Social norms also showed positive relationships with intention, particularly for the "plant-based protein" (r=0.731, p<0.001) and "soy-based protein" (r=0.556, p=0.002) infographics. Infographic presence increased the consumption of soy taco crumble in university dining centers, with twenty consumers compared to nine without the infographic. The final phase focused on developing and scaling up a texturized soy protein taco crumble. The formulation was optimized and evaluated for physicochemical properties such as moisture content, pH, color, cooking loss, and water-holding capacity to ensure product stability and quality under typical dining center conditions. Key physicochemical properties included moisture content (freshly cooked product retained the same moisture during holding for 60 minutes, while refrigerated samples for 3 and 7 days had reduced moisture content), cooking loss (13.22±3.07), and water-holding capacity (96.44±1.14). Sensory evaluations among 208 students and dining center staff using the nine-point Hedonic scale (1=dislike extremely, 9=like extremely) demonstrated high acceptability, particularly for aroma, flavor, and seasonings, with overall acceptability scores of 7.54±1.17. For cooked taco crumble, pH was 6.47±0.12, and color was L*=39.63±4.26, a*=15.64±0.81, and b*=29.35±0.98. Nutritional analysis showed that one serving containing 2 ounces (67g) contained 11 grams of protein, 4 grams of dietary fiber, and 100 calories, with a cost of $0.18 per serving. Over 82% of the students tasting the product were willing to consume the product again in the dining center, with several students commenting that they could not tell the product was plant-based. In conclusion, this research successfully developed a scalable soy taco crumble that aligns with consumer preferences for taste, texture, and sustainability for university students. Through ongoing commitment to product refinement, education, and addressing societal preconceptions, soy-based products can significantly contribute to a diverse and sustainable food ecosystem.
Keywords: Soy-based food; Nutritional awareness; Theory of Planned Behavior; Plant-based meat alternative; Consumer behavior; Sustainable plant-based protein